LINGUISTIC STUDYING UZBEK ETHNOGRAPHIC WORDS - Xasanova Kamila Baxtiyorovna (Western European Studies, 2024)
Today in linguistics is gave a speciai attention to the study of vocabulary with national colours. In this article, we examined the use and study of ethnographic vocabulary in the Uzbek language, examples of scientific works of various linguists , and their distinctive features .
Keywords: Vocabulary; linguistics; aspect; direction